(untitled) (Nóema, 2022)
This essay aims to analyze some instances of the Material Engagement Theory (MET) proposed by Lambros Malafouris in its intersections with speculative philosophy of Alfred North Whitehead. Malafouris does not refer to speculative philosophy as merely support for his theories but rather identifies a number of problems common to the MET and the Whitehead’ philosophy of the organism, which basically revolve around the relationship between noesis and praxis. In detail, the text will focus on the ways in which MET theory calls into question, in an original and fruitful way, the relationship between theory and praxis, by re-actualizing the peculiar way in which Whitehead understands the concept of αἴσθησῐς.